Gait in patients with stroke-related hemiparesis and methods of gait assessment - Guzik, Agnieszka; Wolan-Nieroda, Andżelina; Walicka-Cupryś, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Cerebral stroke, a serious complication of cardiovascular system disorders, has become an important medical issue in contemporary societies. Gait disorders in patients after stroke constitute a serious clinical challenge - every year, more than ten thousand patients become seriously disabled as a result of stroke. Locomotor disability is one of stroke’s consequences. Patients with stroke-related hemiparesis often show gait disorders. Hemiparetic gait is characterized with a number of disorders, such as a considerable asymmetry of gait phase time, i.e. step length, or limb load – the healthy leg being overloaded. These disorders result in limiting patients’ everyday activity. Therefore, objective methods of gait analysis are currently being researched. Among gait assessment methods there are clinical, or observation methods – which consist of gait description as related to the normal gait patterns; as well as quantitative, or objective methods – which consist of measuring, description and analysis of chosen parameters of human gait. The aim of the study is to characterise gait in patients with stroke-related hemiparesis, as well as to discuss the methods of its assessment.

Udar mózgu, będący dramatycznym powikłaniem chorób układu naczyniowego, stanowi duży problem zdrowotny we współczesnym społeczeństwie. U pacjentów z niedowładem połowiczym po udarze mózgu występuje patologiczny wzorzec chodu. Chód hemiparetyczny cechuje się serią zaburzeń, w tym znaczną asymetrią czasu trwania faz chodu, długości kroku, obciążenia kończyn, polegającą na przeciążaniu kończyny zdrowej. Skutkuje to ograniczeniem aktywności w życiu codziennym. Ze względu na narastające znaczenie społeczne i powszechność udaru mózgu coraz częściej poszukuje się metod w zakresie analizy chodu tej grupy chorych. Wśród metod oceny chodu wyróżnia się metody kliniczne, obserwacyjne polegające na opisie chodu w odniesieniu do wzorca prawidłowego oraz metody ilościowe, obiektywne, polegające na pomiarze, opisie i analizie wybranych parametrów charakteryzujących chód człowieka. Celem pracy jest charakterystyka chodu pacjentów z niedowładem połowiczym po udarze mózgu i metod jego oceny.
Chód pacjentów z niedowładem połowiczym po udarze mózgu i metody jego oceny
Keywords: cerebral stroke; hemiparetic gait; gait assessment methods; udar mózgu; chód hemiparetyczny; metody oceny chodu